THE CONTRIBUTION OF ISLAMIC EDUCATION TO THE SUSTAINABLE DEVELOPMENT GOALS: A Multi-Site Study of Madrasas and Islamic Boarding Schools in Indonesia - Supandi, Supandi; Aini, Kurratul (Fakultas Agama Islam Universitas Islam Madura, 2025)
This study aims to analyze the contribution of Islamic education, especially madrassas and Islamic boarding schools, in supporting the achievement of (SDGs) in Indonesia. Using a qualitative approach and a multi-site case study design, the research was conducted on a number of purposively selected madrassas and pesantren based on regional representation, institutional models, and involvement in programs relevant to the SDGs. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed using the Miles & Huberman model with triangulation of sources and methods to maintain validity. The results of the study show that madrasas and pesantren have a dominant contribution to SDG through the provision of affordable, inclusive, and religious value-based education. In addition, Islamic boarding schools play a role in SDG through entrepreneurship training and skills programs, as well as SDG by mainstreaming religious moderation and tolerance. Several institutions also show initiatives related to SDG through the eco/green pesantren program. However, challenges are still faced, such as the quality gap between institutions, the limitation of digital literacy, and the lack of sustainable funding support. This research confirms that Islamic education is not only an agent of the transmission of religious knowledge, but also a strategic actor of sustainable development. To strengthen this contribution, it is necessary to strengthen governance, digital innovation, community economic empowerment, and policy support that is responsive to the global agenda and local needs.